Cálculo de lajes lisas com protensão parcial e limitada - Mello, Ana Lucia Vargas de (Universidade Federal de São Carlos, 2005)
Flat slabs are associated with rationalization, better esthetic conditions and higher speed during construction. The use of post-tension can make this system viable since it strongly improves the structural performance in respect to punching and in case of extreme deflection of the slab. The durability of prestressed concrete elements is assured by meeting their limiting crack requirements. The Brazilian code for structural concrete prescribes the obligation of using limited post-tension, within aggressive environments, and in other cases, partial posttension. The verifications to be made in both cases are different, as well as the calculation procedures. In this particular research, some procedures to determine the number of tendons that are needed for partial and limited post-tension are presented, as well as the wide range of possibilities in the use of quantitative passive and active reinforcements. Possible tendon profiles, horizontal tendon layouts, and the use of bonded or unbonded tendon are also suggested and discussed. All procedures are shown within a numerical example and according to the conditions foreseen in the Brazilian code for structural concrete. Based on the found results, the adopted procedures provided good solutions for design of post-tensioned slabs.
Keywords: Construção civil; Protensão parcial; Protensão limitada; Lajes estruturas; Cálculo; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL